Sistem Pendeteksi Kebakaran Berbasis Internet of Things Menggunakan Webhook Discord dengan Alarm - Hermanto, Hermanto; Kamdan, Kamdan; Maulana, Afrizal (Journal of Information System Research (JOSH), 2025)
Fires are one of the most devastating disasters, often resulting in major losses—both materially and in terms of human lives. To help reduce these risks, a fast and accurate fire detection system is essential. This study presents the development of a fire detection system based on the Internet of Things (IoT), which integrates Discord Webhook notifications and an alarm system, powered by Fuzzy Logic. The system uses flame, smoke, and gas sensors to detect potential fire hazards in an area. Sensor data is processed using Fuzzy Logic to assess the level of fire risk more accurately, and the Center of Gravity (COG) method is used for defuzzification. When a dangerous condition is detected, the system automatically triggers an alarm, a flashing light, and a blower as preventive actions. Thanks to the IoT integration, real-time alerts can be sent via Discord Webhook, keeping users informed instantly. This approach addresses the lack of systems capable of delivering immediate fire warnings. The results of this research show that the system can effectively provide early fire detection with high accuracy and rapid notifications. When both the flame and gas sensors detect danger, a warning is sent to the user through Discord, and users can also review past events through the system’s web server history. Overall, this system offers a practical and innovative solution to improving safety and disaster response.